Systems Thinking in the Circular Economy: An Integrative Literature Review - Nahid Entezarian; Mohammad Mehraeen (Journal of Systems Thinking in Practice)
In this integrative review, the concept of the Circular Economy (CE) is extensively analyzed from the perspective of Systems Thinking (ST) to gain insights into the circular economy. Seventy-two articles from Scopus and Web of Science databases were reviewed to gain a better understanding of the ambivalent nature of circular economy and systems thinking. The main objective of this study is to provide a clear understanding of the circular economy concept through the lens of systems thinking. Therefore, a thematic framework is presented that synthesizes the literature in a tangible form for researchers, practitioners, and policymakers. This review contributes to a better understanding of the circular economy as a complex and dynamic system. It highlights the interdependencies that can arise in the circular economy and emphasizes the need for holistic and systemic approaches to address these challenges. Through this integrative review, six systems thinking applications in the CE are identified, including Stakeholder engagement in decision-making, innovation, and deep transformational change, implementation of circular business models, life cycle management optimization through better resource management, supply chain optimization and reduced unintended consequences and designing sustainable products. This paper contributes to the existing body of knowledge by identifying future research gaps and opportunities to advance in this field of study consistently. It provides a valuable resource for researchers, practitioners, and policymakers seeking to advance the circular economy agenda.